Late potentials abolition reduces ventricular tachycardia recurrence after ablation especially in higher‐risk patients with a chronic total occlusion in an infarct‐related artery. (10th April 2018) - Di Marco, Andrea; Oloriz Sanjuan, Teresa; Paglino, Gabriele; Baratto, Francesca; Vergara, Pasquale; Bisceglia, Caterina; Trevisi, Nicola; Sala, Simone; Marzi, Alessandra; Gulletta, Simone; Cireddu, Manuela; Anguera, Ignasi; et al.
Abstract: Introduction: Late potentials (LP) abolition is recognized as an effective strategy for substrate ablation of ventricular tachycardia (VT). The presence of a chronic total occlusion in a coronary artery responsible for a previous myocardial infarction (infarct related artery CTO, IRA‐CTO) is emerging as a predictor of ventricular arrhythmias and VT recurrence after ablation. We sought to analyze the effects of LP abolition, focusing on the high‐risk subgroup of patients with IRA‐CTO. Methods and results: This was a single‐center, observational study that screened all patients with prior myocardial infarction and clinical VT, referred for VT ablation at San Raffaele Hospital between 2010 and June 2013. Patients were then included in the study if they had a coronary diagnostic angiography (without revascularization) performed during the index hospitalization. The main endpoint was VT recurrence after ablation. Eighty‐four patients formed the population of the study. An IRA‐CTO was present in 47 patients (56%) and the presence of an IRA‐CTO was a predictor of VT recurrence (HR 3.7, P = 0.005). LP were observed in 51 patients and successfully abolished in 38 cases. LP abolition was associated with lower VT recurrence especially among patients with IRA‐CTO (24% vs. 65%, P = 0.005). The presence of an IRA‐CTO, in combination with no LP abolition, was the strongest predictor of VT recurrence (HR 4.4, P < 0.001). Conclusions: Late potentials abolition is an effective strategy for substrate ablation of ventricular tachycardia. The additional reduction of VT recurrence achieved with LP abolition on top of noninducibility is especially significant among high‐risk patients with IRA‐CTO.